Cost-Effectiveness of Adding SGLT2 Inhibitors to Standard Treatment for Heart Failure With Reduced Ejection Fraction Patients in China - Jiang, Yaohui; Zheng, Rujie; Sang, Haiqiang (Frontiers in Pharmacology, 2021)
Objective: To evaluate the economics of adding dapagliflozin or empagliflozin to standard treatment in the treatment of heart failure with reduced ejection fraction (HFrEF) in China. . Methods: A Markov model was developed to project clinical and economic outcomes of adding dapagliflozin or empagliflozin to standard treatment for 66-year-old patients with HFrEF. A cost-utility analysis was performed mostly based on data from the EMPEROR-Reduced trial and the DAPA-HF trial. The primary outcome were total and incremental costs and quality-adjusted life years (QALYs) and the incremental cost-effectiveness ratio (ICER) Results: Compared with the standard treatment, adding dapagliflozin to standard treatment in the treatment of HFrEF in China was more expensive (¥31367.18 vs. ¥23159.84) but more cost-effective (3.87 QALYs vs. 3.64 QALYs), resulting in the ICER of ¥35999.18 per QALY; adding empagliflozin was also more expensive (¥32341.24 vs. ¥26525.46) but more cost-effective (3.66 QALYs vs. 3.53 QALYs), resulting in the ICER of ¥46397.93 per QALY. Sensitivity analysis demonstrated the robustness of the model identifying the cardiovascular death as a significant drivers of the cost-effectiveness. Probabilistic sensitivity analysis indicated that when a willingness-to-pay (WTP) was ¥70892 per QALY, the probability of adding dapagliflozin or enpagliflozin would be cost-effective was 70.5. %, 55.2%, scenario analysis showed that the cost of hospitalization, diabetes status and time horizon had a greater impact on ICER. Conclusion: Compared with standard treatments adding or not adding empagliflozin, adding dapagliflozin to standard treatment in the treatment of HFrEF in China was extremely cost-effective.